Electromyographic correlates of learning during robotic surgical training in virtual reality - Suh, Irene H; Mukherjee, Mukul; Schrack, Ryan; Park, Shi-Hyun; Chien, Jung-Hung; Oleynikov, Dmitry; Siu, Ka-Chun (Studies in health technology and informatics, 2011)
The purpose of this study was to investigate the muscle activation and the muscle frequency response of the dominant arm muscles (flexor carpi radialis and extensor digitorum) and hand muscles (abductor pollicis and first dorsal interosseous) during robotic surgical skills training in a virtual environment. The virtual surgical training tasks consisted of bimanual carrying, needle passing and mesh alignment. The experimental group (n=5) was trained by performing four blocks of the virtual surgical tasks using the da Vinci™ surgical robot. During the pre- and post-training tests, all subjects were tested by performing a suturing task on a "life-like" suture pad. The control group (n=5) performed only the suturing task without any virtual task training. Differences between pre- and post-training tests were significantly greater in the virtual reality group, as compared to the control group in the muscle activation of the hand muscle (abductor pollicis) for both the suture tying and the suture running (p<0.05). In conclusion, changes in electrographic activity shows that training in virtual reality leads to specific changes in neuromotor control of robotic surgical tasks.